Testosterone and Estradiol as Novel Prognostic Indicators for HBV-Related Acute-on-Chronic Liver Failure - Sun, Shuning; Xu, Baoyan; Tan, Wenting; Xiang, Xiaomei; Zhou, Yi; Dan, Yunjie; Guo, Yanzhi; Tan, Zhaoxia; Deng, Guohong (Frontiers in Medicine, 2021)
Background: HBV-related acute-on-chronic liver failure (HBV-ACLF) has a high short-term mortality and urgently needs an early warning system with simplicity and high accuracy. Previous studies show that sex hormones play potential roles in the progression of HBV-related liver diseases. Aims: To explore the effect of testosterone and estradiol on the occurrence and prognosis of HBV-ACLF. Methods: A prospective cohort of 300 chronic hepatitis B (CHB) patients was enrolled among which 108 were diagnosed with HBV-ACLF at admission and 20 developed to HBV-ACLF during hospitalization. We compared the level of serum testosterone and estradiol of patients with varied ACLF background, disease severity and cirrhosis conditions and analyzed the predictive ability of short-term prognosis. A novel prognostic model involving testosterone was developed and further validated in the HBV-ACLF group. Results: The baseline estradiol level of HBV-ACLF group was significantly higher while testosterone was lower than that of non-ACLF group. The estradiol level increased while the testosterone level decreased as the number of organ failures increased. Testosterone had high accuracy in predicting the short-term mortality in HBV-ACLF (AUROC=0.726) and estradiol did better in predicting the occurrence of ACLF during hospitalization (AUROC=0.695).The novel prognostic model involving testosterone (TATIM model) was proved to have considerable prediction efficiency(AUROC=0.828) in HBV-ACLF cohort with or without cirrhosis. Conclusion: Testosterone could be utilized as short-term prognostic indicator for HBV-related ACLF and estradiol can help to predict its occurrence. TATIM model is a novel prognostic model for HBV-related ACLF with simplicity and good performance irrespectively of liver cirrhosis.